Broca's area, sentence comprehension, and working memory: an fMRI study - Rogalsky, Corianne; Matchin, William; Hickok, Gregory (Frontiers in Human Neuroscience, 2008)
The role of Broca's area in sentence processing remains controversial. According to one view, Broca's area is involved in processing a subcomponent of syntactic processing. Another view holds that it contributes to sentence processing via verbal working memory. Sub-regions of Broca's area have been identified that are more active during the processing of complex (object-relative clause) sentences compared to simple (subject-relative clause) sentences. The present study aimed to determine if this complexity effect can be accounted for in terms of the articulatory rehearsal component of verbal working memory.  In a behavioral experiment, subjects were asked to comprehend sentences during concurrent speech articulation which minimizes articulatory rehearsal as a resource for sentence comprehension. A finger-tapping task was used as a control concurrent task. Only the object-relative clause sentences were more difficult to comprehend during speech articulation than during the manual task, showing that articulatory rehearsal does contribute to sentence processing.  A second experiment used fMRI to document the brain regions underlying this effect.  Subjects judged the plausibility of sentences during speech articulation, a finger-tapping task, or without a concurrent task. In the absence of a secondary task, Broca's area (pars triangularis and pars opercularis) demonstrated an increase in activity as a function of syntactic complexity. However, during concurrent speech articulation (but not finger-tapping) this complexity effect was eliminated in the pars opercularis suggesting that this region supports sentence comprehension via its role in articulatory rehearsal.  Activity in the pars triangularis was modulated by the finger-tapping task, but not the speech articulation task.